My Favourite People and Me, 1978 to 1988 - Davies, Alan (London Penguin Books, 2009)
Offers an affectionate trip through a suburban childhood in Essex and an eighties education in Kent.
Keywords: Motion picture actors and actresses -- Nineteen eighties -- Television actors and actresses